Astrocytes: definition, appearance and general physiology 2 - Verkhratsky, Alexei (Henry Stewart Talks, 2022)
Intracellular ionic signalling associated with astroglial excitability, Calcium and sodium ions, Homeostatic membrane transporters, Astrocytes as secretory cells of the CNS, Astrocytes in synaptic transmission, Functional implication of microdomains, Tripartite synapse, Astrocytic synaptic cradle, astrocytes control homeostasis of the CNS